TANTANGAN MANAJEMEN ARSIP ELEKTRONIK DI ERA WEB 2.0 - Mardiati, Wiwiet (UI Scholars Hub, 2015)
From early 1990s, electronic records (e-records) have become a part of daily business activities for both small and big organisations. Since then, Records Management (RM) professionals have aimed to create a consistent and standard way to manage e-records. Nowadays, the challenges for managing e-records have been considerably complicated with the rise of Web 2.0 during the last few years. This paper will point out the challenges in managing electronic records, how RM professionals in Western Australia try to discover the best way to manage them in the Web 2.0 environment, and how it changes the role of the RM professionals in general.